Role of RyR2 Phosphorylation at S2814 During Heart Failure ProgressionNovelty and Significance - Respress, Jonathan L.; Voigt, Niels; Wieland, Thomas; Dobrev, Dobromir (Circulation research, 2012)
Rationale: Increased activity of Ca2+/calmodulin-dependent protein kinase II (CaMKII) is thought to promote heart failure (HF) progression. However, the importance of CaMKII phosphorylation of ryanodine receptors (RyR2) in HF development and associated diastolic sarcoplasmic reticulum Ca2+ leak is unclear. Objective: Determine the role of CaMKII phosphorylation of RyR2 in patients and mice with nonischemic and ischemic forms of HF. Methods and Results: Phosphorylation of the primary CaMKII site S2814 on RyR2 was increased in patients with nonischemic, but not with ischemic, HF. Knock-in mice with an inactivated S2814 phosphorylation site were relatively protected from HF development after transverse aortic constriction compared with wild-type littermates. After transverse aortic constriction, S2814A mice did not exhibit pulmonary congestion and had reduced levels of atrial natriuretic factor. Cardiomyocytes from S2814A mice exhibited significantly lower sarcoplasmic reticulum Ca2+ leak and improved sarcoplasmic reticulum Ca2+ loading compared with wild-type mice after transverse aortic constriction. Interestingly, these protective effects on cardiac contractility were not observed in S2814A mice after experimental myocardial infarction. Conclusions: Our results suggest that increased CaMKII phosphorylation of RyR2 plays a role in the development of pathological sarcoplasmic reticulum Ca2+ leak and HF development in nonischemic forms of HF such as transverse aortic constriction in mice.